Copy or Create? Some Possibilities for Enriching Journalistic Narratives about Science and Technology Based onPress Releases (Intercom - Brazilian Journal of Communication Sciences, 2026)
This study examines how press releases (PRs) are used and how they couldbe improved during the journalistic production process. A sample of 322PRs published in the EurekAlert! repository was examined through contentanalysis, complemented by a sociotechnical approach and observation ofjournalistic production practices. The findings indicate that churnalism (thefull or partial reproduction of the original text) is prevalent: one in four PRs wasreproduced ipsis litteris (verbatim), one in two underwent minor alterations,and one in five received complementary additions that increased its journalisticvalue. The analysis reveals an inverse relationship between the laboriousnessof a strategy and its frequency of use. This is evidenced by the less frequentapplication of more demanding techniques, such as: interviewing researchers not directly involved in the reported work, citing caveats,or warning that results announced at conferences aremerely abstracts of ongoing studies. Expanding upon theseresults, the theoretical and practical framework suggestsnine possibilities for enriching journalistic stories based onPRs. These possibilities emphasize the inclusion of actorsbeyond those directly involved in the research, highlightingtheir connections and the uncertainties regarding the resultsand the continuation of the scientific work.
Keywords: Scientific Journalism; Scientific Dissemination; Actor-Network Theory; Press Releases.